Implementation of File Sharing and Remote Desktop Connection (RDC) by Utilizing Local Area Network (LAN) - Sofyan; Asri, Yessy (LPPM Politeknik Aceh Selatan, 2024)
The exchange of information between devices in a network is very important for efficiency and collaboration. One technology that supports the exchange of information is File Sharing and Remote Desktop Connection (RDC). This research aims to implement these two technologies in a Local Area Network (LAN) to facilitate file exchange and remote access to computer desktops. File sharing allows users to easily share data and resources between computers on a network. This study examines various methods and protocols used in file sharing, such as SMB (Server Message Block) and FTP (File Transfer Protocol), as well as RDC mechanisms such as RDP (Remote Desktop Protocol). This research also explores the security challenges faced in the implementation of these two technologies, including threats to data privacy and the potential for unauthorized access. Implementation begins with a stable and secure LAN network configuration. Then, using file sharing protocols such as SMB (Server Message Block) or NFS (Network File System), users can share and access files between devices on the network easily. Additionally, by utilizing the Remote Desktop Connection service, users can access a computer's desktop remotely from other devices on the network, allowing for efficient system administration as well as access to applications and files located on that desktop. The implementation methods used include configuring network settings, installing and configuring file sharing software and Remote Desktop Connection services, as well as testing to ensure optimal connection and security. Through case studies and experiments, this research proves that the use of LAN as network infrastructure can support high performance and stability in implementing file sharing and RDC. By utilizing a LAN, this research shows that implementing file sharing and RDC can improve operational efficiency and collaboration in the work environment. The results of this implementation are expected to increase productivity and collaboration in a LAN environment by enabling easy and secure access to files and computer desktops from various locations on the network and emphasize the importance of strong security settings and user training to maximize the benefits of this technology in local networks.